Who owns the past? The politics of religious heritage in contemporary India - Ranjan Bandyopadhyay (2018)
© 2016, © Emerald Group Publishing Limited. Purpose: This conceptual paper aims to contribute to the growing literature around the “politics of heritage” by focusing on India which has a multifaceted society with several layers of religious culture and history. Design/methodology/approach: The work is based on an extensive review of the literature and philosophical discussions relating to the politics of heritage tourism and the political dimensions of nationalism and ethnicity from an interdisciplinary perspective. Findings: The main purpose of this conceptual paper is to develop hypotheses. Hence, the study asks: How does postcolonial India reconstruct its past and how are religions represented as part of the national image and for the purpose of tourism promotion? How tourism and religious heritage support a broader secular dreamscape of harmonious cultural nationalism in India? Considering all allegations for supporting the Hindutva movement (who considers Hinduism to be the source of India’s “essential” identity and believes it alone can provide national cohesiveness) by the ruling Bharatiya Janata Party (BJP) government in India, it is worth examining if there are any subtle changes to the tourism agenda created by the new government and the ambivalence surrounding it. Is there any place for the “foreigners” (Muslims and Christians) in Hindutva political ideology? Future scholars can analyze how tourism promotional material represents three major religions in the country by the current Indian Government (i.e. BJP) in its official tourism website: www.incredibleindia.org. This will take “politics of heritage” studies to a different trajectory, as analysis of web media has emerged as a critical medium in understanding numerous social processes. Research limitations/implications: The paper draws on a wide range of seminal work by scholars of nationalism and ethnicity over the past few decades, but it cannot be comprehensive. Originality/value: The paper’s originality lies in its novel approach to an understudied aspect in tourism studies (i.e. politics of heritage) and providing suggestions for future research.